Big Data based Law in the process of forming legislation in Indonesia - PUTRANTO, R.D; PERWIRA, I; DEWI, S; MURWADJI, T (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This paper aims to analyze the urgency of using Big Data in the formation of laws and regulations associated with the principle of forming good legislation. The results indicated that the use of Big Data to capture the aspirations of the people in the process of forming laws and regulations is a real solution to create laws. Its application can be done at the planning, drafting, and discussion stages of each statutory regulation made. Each input will be analyzed by Big Data and then processed into a new output that is concise and easily understood by the legislators.